The Cosmatesque Mosaics of Westminster Abbey The Pavements and Royal Tombs: History, Archaeology, Architecture and Conservation. - Rodwell, Warwick (Oxbow Books, Limited, 2019)
Of proposed phasing -- Notes on the characteristics of each phase -- Early repairs to the Cosmati pavement by Paul Drury -- Phase 2: repairs in sympathy with the primary mosaic work -- Phase 2-3: various interventions, probably between Phases 2 and 3 -- Phase 3: introduction of new designs and more stone types, probably c. 1660-62 -- Phase 4: interventions related to reordering the sanctuary, 1706-07 -- 5 Surveying, analyzing and evaluating the sanctuary and high altar pavements -- Preparatory studies -- Ground-penetrating radar surveys, 2004-05 by Erica Carrick Utsi -- Some GPR basics.